MANAJEMEN PENGELOLAAN LIMBAH - Akhmad Fauzan; Fitriana Meilasari (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2015)
The growth development in various sectors in the city banjarmasin , to spur the needs of natural resources and the possibility of the problems related to environmental conditions , until socioeconomic problems .One effect of development development are increasing waste .And indirectly can cause environmental pollution .One of the way we can do is counseling to residents of management waste management .The purpose of this activity is add insight , knowledge , and scientific for people in doing waste management .The community method of waste management .The result of this activity is the sea belitung understanding how to do waste management so they could reduce pollution .